Influence of hand starting position on radial line bisection - Ricci, Mariateresa; Iavarone, Alessandro; Ilardi, Ciro Rosario; Chieffi, Sergio (Frontiers in Psychology, 2023)
When normal individuals are asked to localize and mark the midpoint of a radial line, they tend to bisect it farther than the true center. It has been suggested that radial misbisection depends on the presence of a visual attentional bias directed towards the far space. The aim of the present study was to investigate whether the localization of the center of radial lines was affected by the starting position of the hand. There were two starting positions: one between the body and the radial line ("near"), the other beyond the radial line ("far"). Thirty-four subjects participated in the experiment.The results showed that (i) participants bisected radial lines farther than the true center, measured with reference to their body, in both near and far condition, and (ii) bisection errors in the near condition were greater than those in the far condition. We suggest that hand starting position and direction of ongoing movement influenced radial line misbisection by modulating visual attentional bias directed to far space.